Microstructure characterization of a duplex stainless steel weld by electron backscattering diffraction and orientation imaging microscopy techniques - Aguiar,Isabela Viegas (2015)
This paper describes the electron backscatter diffraction (EBSD) technique used to characterize the microstructure (especially the morphology and constitution) of the base metal (BM), the heat-affected zone (HAZ) and the fusion zone (FZ) on a lean duplex stainless steel (LDX). This technique provides advantages due to its simplicity of use and greater depth of information, thereby increasing the amount of information obtained by traditional characterization techniques such as optical microscopy (OM), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The use of EBSD together with orientation imaging microscopy (OIM) as a tool to understand phase transformation paths and ferrite-austenite variant selection was discussed. Vickers microhardness measurements were performed and no significance difference between the different zones was found. Orientation distribution function (ODF) results show that there are no significant changes on the crystallographic texture of the samples after welding. The advantages of using SEM together with EBSD for microstructure analyzing and texture development were also discussed.